Timing of first cuddling after preterm birth improved over five decades, while delays were linked to negative maternal experiences - Fieß, Achim; Hartmann, Alica; Schuster, Alexander K.; Ernst, Mareike; Mildenberger, Eva; Wackernagel, Dirk André; Grabitz, Stephanie Desirée; Urschitz, Michael Siegfried; Pfeiffer, Norbert; Beutel, Manfred; Gißler, Sandra; Tesarz, Jonas (Acta paediatrica, 2026)
Aim Early physical contact after birth is critical for families of preterm infants, who face higher risks of psychological stress. This study examined changes in first cuddling over five decades and its relation to parental birth experiences and perceptions of early parenthood. Methods This retrospective cohort study was conducted at the University Medical Center Mainz, Germany. Parents completed questionnaires and structured interviews about birth experiences, timing of first cuddling and perceptions of parenthood. Multivariable logistic regression was used to analyse associations of gestational age and cuddling delay with parental outcomes. Results Data were obtained from 940 mothers and 614 fathers of 1559 children (median age 15 years, range 4-52, 824 female). Time to first cuddling in extremely preterm infants decreased from several weeks in the 1970s to about 1 week in the 2010s. Mothers of preterm or delayed-cuddling infants more often perceived birth as an emergency, felt less prepared for discharge and reported negative feelings towards motherhood. Fathers showed similar but weaker associations. Conclusion The time until first cuddling decreased markedly over five decades, reflecting greater clinical awareness. However, delayed cuddling remained strongly linked to negative maternal perceptions, underlining the importance of prioritising early physical contact in neonatal care.